A Comparative Study of the Chemical Profile from Species of the Bacillus cereus Group - Salazar, Bruno; Vaca, Jessica; Ortiz, Aurelio; Sansinenea, Estibaliz (Letters in Organic Chemistry, 2025)
The Bacillus cereus group includes eight well-characterized and established species, whose classification and identification have been arduous and intense tasks. The similarity between Bacillus cereus group species and the discovery of new strains have complicated their classification and identification. The chemical profile can be complementary, along with molecular methodologies, to classify Bacillus species. With this issue in mind, we performed a comparative study on natural compounds isolated from Bacillus cereus, Bacillus mycoides, Bacillus thuringiensis, Bacillus weihenstephanensis and Bacillus toyonensis. We isolated compounds from Bacillus cereus, Bacillus mycoides, Bacillus thuringiensis, Bacillus weihenstephanensis and Bacillus toyonensis, elucidating their chemical structure by spectroscopic methods. The data suggests that indolic compounds are isolated from B. thuringiensis, preferentially serving to identify this species. Moreover, macrolactin compounds are extremely specific for B. weihenstephanensis since these compounds are not isolated from any other species. Therefore, the chemical profile of each species can be related to a species of this group, helping to define the type of species. In addition, the data achieved suggest that although genomically B. mycoides and B. weihenstephanensis can be indistinguishable, both species should be treated differently.
Keywords: B. weihenstephanensis